Review of the subgenera Metopius Panzer and Peltastes Illiger of the genus Metopius Panzer (Hymenoptera: Ichneumonidae: Metopiinae) from Japan - Morishita, Shunsuke; Watanabe, Kyohei (Zootaxa, 2024)
Japanese species of the subgenera Metopius Panzer and Peltastes Illiger of the genus Metopius Panzer are reviewed. Two species of the former and six species of the latter are recognized in the Japanese fauna. Metopius (M.) anxius Wesmael, 1849, M. (P.) pinatorius Brullé, 1846, and M. (P.) scrobiculatus Hartig, 1838 are newly recorded from Japan. The subgeneric position of M. (Ceratopius) hakiensis Matsumura, 1912 is changed from the subgenus Ceratopius to the subgenus Peltastes. The following three synonyms are proposed: M. (P.) arakawai (Uchida, 1930) = M. (P.) hakiensis; M. (P.) oharai Kusigemati, 1983 = M. (P.) scrobiculatus; Metopius (P.) sapporensis Uchida, 1930 = M. (P.) pinatorius. New distribution records and keys to the Japanese subgenera and species of this genus are also provided.